2019
DOI: 10.1139/cjce-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Integrated predictive artificial neural network fatigue endurance limit model for asphalt concrete pavements

Abstract: Asphalt endurance limit is a strain value if experienced by asphalt pavement layer, no accumulated damage will occur and is directly related to asphalt healing. Therefore, if the pavement experiences this value of strain, or lower, no fatigue damage would accumulate within that pavement section. Beam fatigue test data conducted under the NCHRP Project 9-44A were extracted and utilized to create an artificial neural network predictive model (ANN) to determine the endurance limit strain values for conventional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In addition, the coefficient of determination (R 2 ) was higher for the newly developed ANN than the one developed under the NCHRP project 944-A (0.891). Also, a good correlation between the newly developed model and the ANN model previously developed by Isied and Souliman was found, as demonstrated in Figure 8 (25). This indicates the ability of the developed model to predict EL strain values.…”
Section: Comparison Against the Previously Developed Endurance Limit (El) Prediction Modelssupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, the coefficient of determination (R 2 ) was higher for the newly developed ANN than the one developed under the NCHRP project 944-A (0.891). Also, a good correlation between the newly developed model and the ANN model previously developed by Isied and Souliman was found, as demonstrated in Figure 8 (25). This indicates the ability of the developed model to predict EL strain values.…”
Section: Comparison Against the Previously Developed Endurance Limit (El) Prediction Modelssupporting
confidence: 67%
“…The newly developed EL strain prediction model was compared with the EL prediction model previously developed under the NCHRP project 944-A, as well as the ANN prediction model developed by Isied and Souliman (25). Both models had EL strain prediction equations as shown in Equations 4 and 5, respectively.…”
Section: Comparison Against the Previously Developed Endurance Limit (El) Prediction Modelsmentioning
confidence: 99%
“…By investigating the water damage degree of several expressways in China, some researchers analyzed the internal and external causes of water damage of pavement, and put forward measures to reduce the water damage of pavement from the point of design and construction. Some researchers proposed to use finite element analysis method to study the mechanical mechanism of internal structural failure of asphalt concrete pavement under the combined action of driving load and hydrodynamic pressure [8][9][10][11][12][13]. By comparing the water stability test methods at home and abroad, some researchers put forward the immersion rut test, and tested several commonly used mix structure types at present.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted maximum relative errors for FNN and RBFNN are 19.79% and 31.25%, respectively. Other similar research predicting the fatigue strength as the output of the FNN can be found in previous works 239–249 …”
Section: Review Of Nn Applications In Fatiguementioning
confidence: 81%